2007
DOI: 10.1097/01.nna.0000295612.48065.ff
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Leadership Orientation

Abstract: Many nurse manager orientation programs are loosely structured and fail to provide new managers with the experiences and support that will assure them a smooth transition. The authors describe an orientation program for new nurse managers that combines 3 components-nurse manager competencies, precepting by the nurse manager's supervisor, and written and classroom resources that, together, assure that new managers are ready to face the challenges that await them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Attendance at an orientation programme is supported in the literature (Conley et al . ); however, no timelines for this activity could be found. Ongoing funding and flexible scheduling for first‐line nurse managers to attend education programmes would promote continued learning and the development of required skill sets.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Attendance at an orientation programme is supported in the literature (Conley et al . ); however, no timelines for this activity could be found. Ongoing funding and flexible scheduling for first‐line nurse managers to attend education programmes would promote continued learning and the development of required skill sets.…”
Section: Discussionmentioning
confidence: 96%
“…At the organisational level, policy that articulates expectations and timelines for first-line nurse managers to attend an orientation programme during their probationary period is needed. Attendance at an orientation programme is supported in the literature (Conley et al 2007); however, no timelines for this activity could be found. Ongoing funding and flexible scheduling for first-line nurse managers to attend education programmes would promote continued learning and the development of required skill sets.…”
Section: Implications For Nursing Managementmentioning
confidence: 99%
“…A successful role transition or onboarding is essential for an NP to become a competent independent provider as quickly and positively as possible 4 . Structured orientation and onboarding processes foster a smoother transition for new nurses 5 . Orientation is a 1-time event that typically takes place during the 1st few days of a new hire's employment to help familiarize the new employee with the company's values, mission, and culture 6 .…”
mentioning
confidence: 99%
“…The focus of these programs is on the essential management skills and the development of an understanding of the manager's role within the organizational vision and goals. 2 These interactive programs include leadership simulation computer videos that provide viewers with the opportunity to see how techniques can be used through modeling of roles in real-life scenarios. Additionally, many of these programs provide detailed information on managing the business aspects of a health care environment such as fiscal management, quality improvement, and strategic planning.…”
Section: Best Practices In Critical Carementioning
confidence: 99%
“…2011;31 [5]:58-63) of managers because it provides a foundation for the establishment of successful relationships among staff and management. 2,4,5 Currently, many programs integrate interactive computer programs with didactic content. The focus of these programs is on the essential management skills and the development of an understanding of the manager's role within the organizational vision and goals.…”
Section: Best Practices In Critical Carementioning
confidence: 99%